Use of pyriproxyfen in control of Aedes mosquitoes: A systematic review. - John Christian Hustedt; Ross Boyce; John Bradley; Jeffrey Hii; Neal Alexander (Public Library of Science (PLoS), 2020)
Dengue is the most rapidly spreading arboviral disease in the world. The current lack of fully protective vaccines and clinical therapeutics creates an urgent need to identify more effective means of controlling Aedes mosquitos, principally Aedes aegypti, as the main vector of dengue. Pyriproxyfen (PPF) is an increasingly used hormone analogue that prevents juvenile Aedes mosquitoes from becoming adults and being incapable of transmitting dengue. The objectives of the review were to (1) Determine the effect of PPF on endpoints including percentage inhibition of emergence to adulthood, larval mortality, and resistance ratios; and (2) Determine the different uses, strengths, and limitations of PPF in control of Aedes. A systematic search was applied to Pubmed, EMBASE, Web of Science, LILACS, Global Health, and the Cochrane database of Systematic Reviews. Out of 1,369 records, 90 studies met the inclusion criteria. Nearly all fit in one of the following four categories 1) Efficacy of granules, 2) Auto-dissemination/horizontal transfer, 3) use of ultra-low volume thermal fogging (ULV), thermal fogging (TF), or fumigant technologies, and 4) assessing mosquito resistance. PPF granules had consistently efficacious results of 90-100% inhibition of emergence for up to 90 days. The evidence is less robust but promising regarding PPF dust for auto-dissemination and the use of PPF in ULV, TF and fumigants. Several studies also found that while mosquito populations were still susceptible to PPF, the lethal concentrations increased among temephos-resistant mosquitoes compared to reference strains. The evidence is strong that PPF does increase immature mortality and adult inhibition in settings represented in the included studies, however future research should focus on areas where there is less evidence (e.g. auto-dissemination, sprays) and new use cases for PPF. A better understanding of the biological mechanisms of cross-resistance between PPF, temephos, and other insecticides will allow control programs to make better informed decisions.